Beyond Obama's red lines : the Syrian Arab Army and chemical warfare - Kasapoğlu, Can (2019)
Zusammenfassung: The Syrian Arab Army’s chemical warfare capacity has been a game-changer throughout the civil war. Unlike intelligence estimates, Bashar al-Assad’s military planners considered these deadly weapons to be tactical arms for battlefield use, rather than last-resort strategic assets. During the reconstruction period, the West should pursue a comprehensive approach to address issues concerning Syria’s weapons of mass destruction